2022
DOI: 10.3390/biom12010135
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Structural Proteomics for Metal Ion/Protein Binding Studies

Abstract: Metal ions are critical for the biological and physiological functions of many proteins. Mass spectrometry (MS)-based structural proteomics is an ever-growing field that has been adopted to study protein and metal ion interactions. Native MS offers information on metal binding and its stoichiometry. Footprinting approaches coupled with MS, including hydrogen/deuterium exchange (HDX), “fast photochemical oxidation of proteins” (FPOP) and targeted amino-acid labeling, identify binding sites and regions undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 150 publications
(198 reference statements)
0
7
0
Order By: Relevance
“…Variable stoichiometry combinations of hetero‐dodecamers from 12:0 to 0:12 were identified by nMS, SID for each individual hetero‐dodecamers further revealed the lateral symmetry in the subunit arrangement, greatly improve the understanding of catalytic mechanism of PDX heterocomplexes and further explain the correlation between the catalytic activity with PDX1.2‐PDX1.3 stoichiometry (Novikova et al, 2021). Additionally, Lin and co‐workers (Lin & Gross, 2022) recently found that the sialyation, especially Neu5Gc, can stabilize transferrin conformation and inhibit its dimerization, furtherly improving its association with iron and Aβ, ultimately resulting in the transferrin‐mediated Aβ‐iron cellular co‐transporting.…”
Section: Applicationsmentioning
confidence: 99%
“…Variable stoichiometry combinations of hetero‐dodecamers from 12:0 to 0:12 were identified by nMS, SID for each individual hetero‐dodecamers further revealed the lateral symmetry in the subunit arrangement, greatly improve the understanding of catalytic mechanism of PDX heterocomplexes and further explain the correlation between the catalytic activity with PDX1.2‐PDX1.3 stoichiometry (Novikova et al, 2021). Additionally, Lin and co‐workers (Lin & Gross, 2022) recently found that the sialyation, especially Neu5Gc, can stabilize transferrin conformation and inhibit its dimerization, furtherly improving its association with iron and Aβ, ultimately resulting in the transferrin‐mediated Aβ‐iron cellular co‐transporting.…”
Section: Applicationsmentioning
confidence: 99%
“…For more discussion of this point, we cite a recent review of our efforts to understand metal-ion interactions by MS-based footprinting and HDX. 35 ■ EXPERIMENTAL PROCEDURES Materials. All chemicals, proteases, and solvents were purchased from Sigma-Aldrich (St. Louis, MO) unless otherwise stated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These techniques induce fragmentation of the peptide without major scrambling of hydrogen and deuterium, permitting the location of deuterium to be accurately determined. 15 A recent study by the FDA 16 monitored, using HDX-MS, changes in solvent accessibilities of stressed mAbs relative to an unstressed control incubated at 25 ± 2 °C, 60 ± 5% relative humidity (RH) for 6 months. Although this study provided a broad survey across several antibodies, there are still challenges to improving the spatial resolution (i.e., peptide length or number of unique peptides) and to employing robust statistical analysis for accurate and reliable measurements of subtle structural changes by using HDX-MS methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tandem MS (MS/MS) fragmentation such as electron transfer dissociation, electron capture dissociation, and ultraviolet photon dissociation may also be adopted. These techniques induce fragmentation of the peptide without major scrambling of hydrogen and deuterium, permitting the location of deuterium to be accurately determined . A recent study by the FDA monitored, using HDX-MS, changes in solvent accessibilities of stressed mAbs relative to an unstressed control incubated at 25 ± 2 °C, 60 ± 5% relative humidity (RH) for 6 months.…”
Section: Introductionmentioning
confidence: 99%